2023
DOI: 10.1093/europace/euad086
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intracardiac echocardiography–guided zero-fluoroscopic cryoballoon ablation for atrial fibrillation: a prospective randomized controlled trial

Abstract: Aims The development of intracardiac echocardiography (ICE) has enabled fluoroless atrial fibrillation (AF) ablation using three-dimensional electroanatomical mapping systems. However, fluoroless cryoballoon ablation (CBA) remains challenging, mainly because of the lack of a visual mapping system. Hence, this study aimed to investigate the safety and efficacy of fluoroless CBA for AF under ICE guidance. Methods and results Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…7,8 A recent randomized trial examining the feasibility of ICE-guided CBA without fluoroscopy demonstrated significantly decreased radiation with similar success rates and no difference in complications. 9 In the current study, Pongratz et…”
Section: Cabana Trial (Catheter Ablation Versus Antiarrhythmic Drugmentioning
confidence: 54%
See 1 more Smart Citation
“…7,8 A recent randomized trial examining the feasibility of ICE-guided CBA without fluoroscopy demonstrated significantly decreased radiation with similar success rates and no difference in complications. 9 In the current study, Pongratz et…”
Section: Cabana Trial (Catheter Ablation Versus Antiarrhythmic Drugmentioning
confidence: 54%
“…Two large observational studies suggest ICE use in RF ablation is associated with a significant decrease in procedural complications, lower in‐hospital mortality, and shorter hospital length of stay but higher procedural cost 7,8 . A recent randomized trial examining the feasibility of ICE‐guided CBA without fluoroscopy demonstrated significantly decreased radiation with similar success rates and no difference in complications 9 . In the current study, Pongratz et al elegantly describe similar findings of decreased complications and higher acute success rate with decreased radiation exposure associated with ICE use.…”
mentioning
confidence: 99%
“…Recently Ahn, et al 9 . have shown that zero‐fluoroscopy cryoballoon ablation for AF is feasible without compromising acute and long‐term success or complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Além dos benefícios da redução da exposição ao RX o método “zero fluoro” permite reduzir o risco de problemas ortopédicos pela não necessidade dos aventais de chumbo. 8 , 9 Além destas, uma aplicação validada recentemente é a utilização do EIC para a investigação da presença de trombos, principalmente no apêndice atrial esquerdo, antes da realização de ablação de FA, prescindindo do eco tranesofágico. A técnica foi validada recentemente com o posicionamento do cateter do EIC na artéria pulmonar com demonstração de equivalência quando comparada com o eco transesofágico.…”
unclassified
“…In addition to the benefits of reducing exposure to X-rays, the “zero fluoro” method allows for reducing the risk of orthopedic problems by not requiring lead aprons. 8 , 9 In addition to these, a recently validated application is the use of ICE to investigate the presence of thrombi, mainly in the left atrial appendage, before performing AF ablation, dispensing with transesophageal echo. The technique was recently validated with the positioning of the ICE catheter in the pulmonary artery, demonstrating equivalence when compared with the transesophageal echo.…”
mentioning
confidence: 99%